Investigating the Water Relations in Aqueous Extract Powders of Mango (Mangifera indica) Peel and Seed Waste for Their Use in Food Matrices as a Value-Added By-Product - Ronald Marsiglia-Fuentes; Amparo Chiralt; Luis A. García-Zapateiro (Foods, 2023)
This study investigated the potential uses of discarded mango peel and seed parts by analyzing their water sorption behavior, hydration kinetics, and stability when converted into extract powders at pH 3 and 10. The results revealed that peel extracts had a higher water adsorption capacity compared with seed extracts due to differences in their composition. Peel extracts were primarily composed of carbohydrates (approximately 75%) with a low protein content, while seed extracts contained fewer carbohydrates (less than 30%) but higher levels of proteins (more than 30%) and lipids. The critical water content for maintaining the glassy state of peel extract powders during storage was found to be 0.025 and 0.032 g of water/g for extracts obtained at pH 3 and 10, respectively. In contrast, the Tg values of seed extracts remained relatively unchanged across different water content levels, suggesting that proteins and lipids inhibited the water’s plasticizing effect in the solid matrix. These findings indicate that both mango waste fractions exhibit distinct hygroscopic behaviors, necessitating different approaches to processing and utilization. These extracts hold potential applications for various food products such as beverages, gels, sauces, or emulsions, contributing to the reduction in waste and the creation of value-added products from mango residues.